Theatre in Education: The Implementation of Improvisation in Dialogue Pronunciation Technique in Teaching - Muhammad Faisal, Ahmad; Zolkipli, Abdullah; Abdul Walid, Ali (Human Resource Management Academic Research Society, 2021)
The improvisation in dialogue pronunciation will give significance based on the suitability of its application in teaching contexts. Copying, repetition, appreciation, action and reaction are the elements included in the techniques practised in acting. This study is fully dedicated to the implementation of dialogue pronunciation through improvisation technique which is often highlighted for the actors and actresses in acting. However, what goes unnoticed is the fact that the way a teacher delivers a lesson in a classroom has similarities in function and role as a stage performer. Voice is the main instrument which needs to be used during the whole lesson or performance. The problem statement in this study can be seen from the inability of the teacher to apply an effective dialogue projection technique in their lesson, causing a somber and gloomy classroom. Apart from that, understanding the teaching content alone is not enough if dialogue pronunciation is unclear throughout the lesson. Therefore, this study aims to give exposure on the techniques and introduction to voice mechanism so that the lesson can be delivered more effectively and interesting by the teachers. The process of this study leads towards qualitative form guided by observation and open interviews to review the current teaching methods as well as using suitable library and database references. The result of this study shows the importance of understanding the improvisation in dialogue pronunciation in teaching which can be implemented consciously in teaching and learning process in school.